2022
DOI: 10.3390/cancers14153685
|View full text |Cite
|
Sign up to set email alerts
|

Human Malignant Rhabdoid Tumor Antigens as Biomarkers and Potential Therapeutic Targets

Abstract: Introduction: Atypical teratoid rhabdoid tumor (ATRT) is a lethal type of malignant rhabdoid tumor in the brain, seen mostly in children under two years old. ATRT is mainly linked to the biallelic inactivation of the SMARCB1 gene. To understand the deadly characteristics of ATRT and develop novel diagnostic and immunotherapy strategies for the treatment of ATRT, this study investigated tumor antigens, such as alpha-fetoprotein (AFP), mucin-16 (MUC16/CA125), and osteopontin (OPN), and extracellular matrix modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…However, this was not the case in univariate analysis. We believe this is probably due to the aggressive nature of ATRT [31, 35]. In addition, different genetic studies have shown that the supratentorial and infratentorial tumors have varying genetic profiles that might contribute to OS [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was not the case in univariate analysis. We believe this is probably due to the aggressive nature of ATRT [31, 35]. In addition, different genetic studies have shown that the supratentorial and infratentorial tumors have varying genetic profiles that might contribute to OS [35].…”
Section: Discussionmentioning
confidence: 99%
“…Research is also being conducted to investigate the benefits of molecular-based targeted therapies and immunomodulator therapies [29][30][31]. In a preclinical study conducted by Jayanthan et al [32], they explored the potential of multikinase inhibitors in treating ATRT.…”
Section: Discussionmentioning
confidence: 99%
“…GLI1 protein expression was lower in Epi-iPSC-SP, EC6A-SP, and EC7A-SP when compared to the ATRT cell lines. Interestingly, GLI2, NPM, and Osteopontin proteins were expressed by all cells, which are putative ATRT biomarkers [ 34 , 35 ]. Finally, Pax-6 expression was higher in ATRT cell lines and EC7A-SP but lower in Epi-iPSC-SP and EC6A-SP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The approach used in this study did not require animals but the early-stage cerebellum differentiation protocol to generate spheroids [ 41 ]. The model's gene expression profile showed high similarity with that of patient-derived ATRT cell lines, including upregulated SHH and β-catenin pathway [ 4 ], higher expression of OCT4 and NANOG embryonic markers [ 42 ], higher OPN [ 34 ], as well as a lower level of specific neuronal marker ENO2 ( Fig. 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation